2022
DOI: 10.1155/2022/9416825
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Roles of circCASP9 in Gastric Cancer Based on a circRNA-miRNA-mRNA Regulatory Network

Abstract: Accumulating evidence demonstrates that circular RNAs (circRNAs) have substantial effects on gastric cancer (GC) tumorigenesis and development. In this study, we performed a screen and identified two differentially expressed circRNAs (circCASP9 and circDLG5) from our circRNA microarray. We validated the expression of circCASP9 and circDLG5 in GC tissues and their normal counterparts by using qRT-PCR. Only circCASP9 was revealed to be downregulated in tumor tissues compared with adjacent normal tissues. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Significant geographical differences in the prevalence of gastric cancer have been identified by epidemiological studies (Xie et al 2020 ). Notably, there is a clear link between the frequency of H. pylori infection and locations with the greatest incidence, especially in East Asia (Qin et al 2022 ; Peng et al 2022 ). Gastritis, which is viewed as a crucial stage in gastric carcinogenesis, is frequently present before the onset of gastric cancer (McClain et al 2017 ; Watari et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant geographical differences in the prevalence of gastric cancer have been identified by epidemiological studies (Xie et al 2020 ). Notably, there is a clear link between the frequency of H. pylori infection and locations with the greatest incidence, especially in East Asia (Qin et al 2022 ; Peng et al 2022 ). Gastritis, which is viewed as a crucial stage in gastric carcinogenesis, is frequently present before the onset of gastric cancer (McClain et al 2017 ; Watari et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are circular, noncoding RNAs that arise through backsplicing of precursor mRNAs [7]. They can "sponge" microRNAs [8,9] or interact with RNA-binding proteins [10] to regulate cell proliferation, differentiation, migration, and apoptosis, thereby influencing tumor progression [11]. One class of RNA-binding proteins is ribosomal proteins, which form part of ribosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, circRNAs are the most common as competing endogenous RNAs. At this time, the circRNA sponge absorbs miRNAs, thereby regulating the downstream target genes of miRNAs [ 13 ]. Interestingly, we found that circ_0052184 had the most elevated expression in colorectal cancer, and circ_0052184 was a molecular sponge of miR-604.…”
Section: Introductionmentioning
confidence: 99%